Intraseasonal and interannual variabilities of saltwater intrusion during dry seasons and the associated driving forcings in a partially mixed estuary. (15th February 2019) - Lin, Zhongyuan; Zhang, Heng; Lin, Hongyang; Gong, Wenping
Abstract: Saltwater intrusion is a major environmental problem in many estuaries worldwide, including Modaomen Estuary in China's Pearl River Delta. It varies in multiple time-scales and is regulated by many external forcings. Here we focus on its intraseasonal and interannual variabilities in dry seasons and their relationships with external forcings. Empirical orthogonal function analysis (EOF) and multiple linear regression analysis are used to investigate the effects of river discharge, tides, and winds on saltwater intrusion from 2004 to 2016 based on daily observation data. On the intraseasonal timescale, tidal range has the largest influence, followed by river discharge and winds, and the effect of the alongshore winds is greater than that of the cross-shore winds. On the interannual timescale, river discharge contributes 57% of the variance for the saltwater intrusion and plays the most important role, while tidal range has a negligible impact. The effect of winds contributes 13% of the variance, and the effect of the cross-shore winds is larger than that of the alongshore ones. A combination of river discharge, tidal range, and winds explains 71% of the saltwater intrusion variance. The interannual variability of saltwater intrusion is also found to be correlated with ENSO, with the correlation coefficient reaching as high as 0.48. In most El Niño/La Niña events there are more/less river discharge, stronger Easterly/Northeasterly winds, and less/more saltwater intrusion in Modaomen Estuary. The findings of our study shed light on the long-term variability of saltwater intrusion in other estuaries. Highlights: Intraseasonal and interannual variabilities of saltwater intrusion are studied. On the intraseasonal timescale, tidal range has the largest influence. On the interannual timescale, river discharge plays the most important role. The interannual variability of saltwater intrusion is correlated with ENSO.